Construção de sentidos e medicalização do sofrimento: uma análise da experiência dos usos de psicofármacos - Corban, Indira (2015)
The increasing use of psychiatric medication points towards a cultural change on how the suffering and treatment of psychological distress is experienced by individuals and embodied their subjectivities. The aim of this work is to analyze the narratives of individuals who make use of psychiatric medication (specially those classified as anxiolytics or antidepressants), in an attempt to understand their own methods of experiencing ongoing medical treatments. Leading off with the theoric-methodological choice of phenomenology, this study tries to understand the experience of psychiatric medication users and comprehend the significance assigned by this people to the consumption of the aforementioned substances. It also pretends to address the processes of (re)signification and generation of subjective meanings relating to suffering and the agent's reflexivity. In order to achieve that, the methodology was based on semiinstructured interviews and life stories of a wide range of individuals off Norteasthern capitals João Pessoa and Recife.